2009
DOI: 10.1021/jm9003413
|View full text |Cite
|
Sign up to set email alerts
|

χ-Conopeptide Pharmacophore Development: Toward a Novel Class of Norepinephrine Transporter Inhibitor (Xen2174) for Pain

Abstract: Norepinephrine (NE) amplifies the strength of descending pain inhibition, giving inhibitors of spinal NET clinical utility in the management of pain. chi-MrIA isolated from the venom of a predatory marine snail noncompetitively inhibits NET and reverses allodynia in rat models of neuropathic pain. An analogue of chi-MrIA has been found to be a suitable drug candidate. On the basis of the NMR solution structure of this related peptide, Xen2174 (3), and structure-activity relationships of analogues, a pharmacoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 58 publications
4
77
0
5
Order By: Relevance
“…For instance, ω-conotoxin MVIIA [C(6)C(6)CC(3)C(4)C] (the only FDA-approved venomderived synthetic peptide, marketed under the name Prialt) (53) and ω-conotoxin CVID [C(6)C(6)CC(3)C(6)C] (phase II clinical trials) (54) both contain the inhibitor cystine knot (ICK) motif where cysteine residues are disposed in a C-C-CC-C-C pattern with a I-IV, II-V, III-VI connectivity. Also, conotoxins such as χ-conotoxin MrIA [(3)CC(4)C(2)C; I-III, II-IV; phase II] are important drug leads (55). Despite a weak correlation between gene superfamilies and pharmacological properties, some functional redundancy among members of a same superfamily exists (56).…”
Section: Significancementioning
confidence: 99%
“…For instance, ω-conotoxin MVIIA [C(6)C(6)CC(3)C(4)C] (the only FDA-approved venomderived synthetic peptide, marketed under the name Prialt) (53) and ω-conotoxin CVID [C(6)C(6)CC(3)C(6)C] (phase II clinical trials) (54) both contain the inhibitor cystine knot (ICK) motif where cysteine residues are disposed in a C-C-CC-C-C pattern with a I-IV, II-V, III-VI connectivity. Also, conotoxins such as χ-conotoxin MrIA [(3)CC(4)C(2)C; I-III, II-IV; phase II] are important drug leads (55). Despite a weak correlation between gene superfamilies and pharmacological properties, some functional redundancy among members of a same superfamily exists (56).…”
Section: Significancementioning
confidence: 99%
“…Pharmacophore models have lead to the discovery of XEN2174 compounds as Norepinephrine Transporter (NETa) and are in phase II clinical trials as pain killer (34). Pharmacophores have been developed for screening transforming growth factor b (ALK5) receptor inhibitors (35), Checkpoint1 kinase inhibitors (36) by retrieving potent molecules from potent databases like specs, NCI, Maybridge, and CNPD.…”
Section: Resultsmentioning
confidence: 99%
“…The most active analogues 7 and 9 were also equally active compared with MrIA in a neuropathic pain study using a rat model sciatic nerve injury assay (Fig 5,6S). [19] The activity loss in 2-5 is due to the sensitivity of the turn region to topological changes, [19][20] likely to occur when introducing a 1,2,3-triazole ring in place of the Cys4-Cys10 disulfide bond. The triazole orientation appears to be of importance for NET activity (compare the more potent peptides 7, 9 with 6, 8).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the length of the bridge, which differed by one CH2 group, plays a minor role (compare 7 vs. 9). These structural effects, were studied by secondary H NMR shift comparison [19] of MrIA and analogues 2-9; this demonstrated that inactive analogues 2-5 suffer from strong perturbation of the overall backbone structure ( Figure 1A). In contrast, active analogues 6-9 showed good H shift correlation compared to MrIA, particularly in the critical GYKL turn region [20] ( Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation